Optimizing The Role of The North Minahasa Regency’s Pamong Praja Police Unit - Najoan, Boby Herke; Masengi, Evi Elvira; Kandou, Selpius (Technium Social Sciences Journal, 2024)
The objectives of the research are 1) To find out how the Pamong Praja Police Unit (Satpol PP) behaves as a Public Servant in curbing illegal traders in the Pedestrian Area of Airmadidi Market, North Minahasa Regency; 2) To find out what is hindering the Pamong Praja Police Unit in controlling illegal traders in the pedestrian area of Airmadidi Market, North Minahasa Regency. Researchers used qualitative research methods with snowball sampling techniques. The results of the research show that 1) activities to control Street Vendors (PKL) on the roads and sidewalks (Pedestrian) of the Airmadidi market by the Pamong Praja Police Unit of North Minahasa Regency have been carried out but are not yet optimal due to a lack of knowledge, street vendors, lack of understanding of the function of roads and sidewalk. Not all street vendors understand the regulations of the North Minahasa regional government, even though they have been socialized; 2) Understanding of the community, street vendors, and members of the Pamong Praja Police Unit regarding their respective roles as obligations which has resulted in the implementation of street vendor control activities not being optimal; 3) The control of street vendors has not been achieved and is not yet optimal due to inhibiting factors, including a lack of qualified human resources, inadequate infrastructure and limited operational costs; 4) Satpol PP's behavior in taking action against street vendors who violate regional regulations always starts with direction and guidance through good communication; 5) Action against street vendors who violate regional regulations selling in the Airmadidi Market district is carried out through warnings in accordance with the established SOP.